Early combined treatment with sildenafil and adipose-derived mesenchymal stem cells preserves heart function in rat dilated cardiomyopathy - Lin, Yu-Chun (BioMed Central, 2010)
BACKGROUND: We investigated whether early combined autologous adipose-derived mesenchymal stem cell (ADMSC) and sildenafil therapy offers an additive benefit in preserving heart function in rat dilated cardiomyopathy (DCM). METHODS: Adult Lewis rats (n = 8 per group) were divided into group 1 (normal control), group 2 (saline-treated DCM rats), group 3 [2.0 × 10(6 )ADMSC implanted into left ventricular (LV) myocardium of DCM rats], group 4 (DCM rats with sildenafil 30 mg/kg/day, orally), and group 5 (DCM rats with combined ADMSC-sildenafil). Treatment was started 1 week after DCM induction and the rats were sacrificed on day 90. RESULTS: The results showed that mitochondrial protein expressions of connexin43 and cytochrome-C were lowest in group 2, and lower in groups 3 and 4 than in group 5 (p < 0.002). Conversely, oxidative index was highest in group 2, and also higher in groups 3 and 4 than in group 5 (p < 0.0003). The mRNA expressions of interleukin (IL)-10, Gro/IL-8, endothelial nitric oxide synthase, and Bcl-2 were lowest in group 2, and lower in groups 3 and 4 compared with group 5 (p < 0.0001). The mRNA expressions of matrix metalloproteinase-9, Bax, caspase 3, and stromal-cell derived factor-1α were highest in group 2, and higher in groups 3 and 4 than in group 5 (p < 0.0004). Apoptosis and fibrosis in LV myocardium were most prominent in group 2 and higher in groups 3 and 4 than in group 5, whereas angiogenesis and LV ejection fraction were lowest in group 2 and lower in groups 3 and 4 than in group 5 (p < 0.003). CONCLUSION: Early combined ADMSC/sildenafil is superior to either treatment alone in preserving LV function.